Theseus-Perseus - Στεφανίδης, Μενέλαος Δημ. (Greek mythology : Heroes, 1992)
Aegeus, son of Pandion, was a king of Athens who is chiefly remembered because he is said to have been the father of the renowned hero Theseus — though whether Theseus really was his son is a matter of dispute.